Planothidium galaicum sp. nov. (Bacillariophyta, Achnanthidiaceae), a new diatom species from Galician coast, Spain - Álvarez-Blanco, Irene; Blanco, Saúl (Phytotaxa, 2013)
A new Planothidium species, Planothidium galaicum sp. nov. is described on the basis of light and electron microscopy investigations of its frustule morphology. This diatom was found in the epiphyton of Himanthalia elongata at Muxía coast (Galicia, northwest Spain). A discussion of the morphological features of this taxon and their taxonomic affinities with related species, is presented.